Myelin-specific T cells carry and release magnetite PGLA–PEG COOH nanoparticles in the mouse central nervous system 1. Issue 2 (3rd January 2018) - D'Elios, M. M.; Aldinucci, A.; Amoriello, R.; Benagiano, M.; Bonechi, E.; Maggi, P.; Flori, A.; Ravagli, C.; Saer, D.; Cappiello, L.; Conti, L.; Valtancoli, B.; et al.
Abstract : Magnetite nanoparticles enter non-phagocytic myelin-specific T cells and reach the central nervous system after in vivo transfer. Abstract : Progress in nanotechnology has determined new strategies concerning drug delivery into the central nervous system for the treatment of degenerative and inflammatory diseases. To date, brain targeting through systemic drug administration, even in a nano-composition, is often unsuccessful. Therefore, we investigated the possibility of loading T lymphocytes with PGLA–PEG COOH magnetite nanoparticles (30 nm), which can be built up to easily bind drugs and monoclonal antibodies, and to exploit the ability of activated T cells to cross the blood–brain barrier and infiltrate the brain parenchyma. Iron oxide nanoparticles have been widely used in biomedical applications due to their theranostic properties and are therefore a well-established nanomaterial. The magnetite core is easily hybridized with polymeric compounds that may enhance the possibility of the nanoparticles entering cells with low phagocytic properties. Taking advantage of these material characteristics, after in vitro assessment of the viability and functionality of nano-loaded MOG35–55 specific T cells, we transferred cells containing the nano-cargo into naïve mice affected by experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis. By means of histological and immunohistological methods, we were able to identify the nano-loaded T cells in the central nervous system. Our data demonstrated that T cells containing nanomaterials hold the possibility of carrying and releasing nanoparticles in the brain.